Metal oxide-promoted hydrodeoxygenation activity of platinum in pt-mox/al2o3 catalysts for green diesel production - Janampelli, Sagar; Darbha, Srinivas (Energy & Fuels, 2018)
Catalytic deoxygenation of fatty acids into renewable hydrocarbons (green diesel) was investigated over 4Pt-8MO(x)/Al2O3 (M = Mo, Re, W, and Sn) catalysts prepared by the wet impregnation method. Platinum deposited on MOx-modified gamma-Al2O3 showed higher catalytic hydrodeoxygenation activity than that of the "neat" Pt/Al2O3 catalyst. The promotional effect of metal oxides (MOx) decreased in the following order: MoOx > ReOx > WOx > SnOx. Characterization studies revealed that metal oxides affect the textural and electronic properties of Pt. Supported Pt facilitated the reduction of these metal oxides. Synergy and electronic contact between Pt and MOx determined the catalytic deoxygenation performance. Fatty acid conversion increased with increasing metallic nature (decreasing binding energy) of Pt. Hydrodeoxygenation product selectivity correlated with the extent of metal oxide reduction. Among the catalysts, 4Pt-8MoO(x)/Al2O3 had the optimum dispersion, electron-rich Pt, and reduced Mo5+ species, enabling quantitative conversion of oleic acid with 93.5% octadecane selectivity at a temperature as low as 220 degrees C and 20 bar hydrogen pressure. Metal oxide switched the mechanism of deoxygenation from decarbonylation/decarboxylation to hydrodeoxygenation. Fatty acids, methyl oleate, and vegetable oil were deoxygenated with equal efficiency over this catalyst. Catalysts were reusable in recycling studies only at higher temperature (320 degrees C) and not at lower temperature (260 degrees C), perhaps due to strong sticking of reactant molecules at lower temperature on the catalyst surface than at higher temperature.